Early Origins of Body Mass in Later Life: Examining Childhood Risks and Adult Pathways. (June 2021) - Mustillo, Sarah A.; Li, Miao; Morton, Patricia; Ferraro, Kenneth F.
Prior research reveals that negative early-life experiences play a major role in the development of obesity in later life, but few studies identify mechanisms that alter the lifetime risk of obesity. This study examines the influence of negative childhood experiences on body mass index (BMI) and obesity (BMI ≥30) during older adulthood and the psychosocial and behavioral pathways involved. Using a nationally representative sample, we examine the influence of cumulative misfortune as well as five separate domains of misfortune on BMI and obesity. Results show that four of the five domains are associated with BMI and obesity either directly, indirectly, or both. The influence of cumulative misfortune on the outcomes is mediated by three adult factors: socioeconomic status, depressive symptoms, and physical activity. The mediators identified here provide targets for intervention among older adults to help offset the health risks of excess BMI attributable of early-life exposure to misfortune.